Spasticity and spastic dystonia: the two faces of velocity-dependent hypertonia. (December 2017) - Marinelli, Lucio; Currà, Antonio; Trompetto, Carlo; Capello, Elisabetta; Serrati, Carlo; Fattapposta, Francesco; Pelosin, Elisa; Phadke, Chetan; Aymard, Claire; Puce, Luca; Molteni, Franco; Abbruzzese, Giovanni; et al.
Abstract: Background: Spasticity and spastic dystonia are two separate phenomena of the upper motor neuron syndrome. Spasticity is clinically defined by velocity-dependent hypertonia and tendon jerk hyperreflexia due to the hyper-excitability of the stretch reflex. Spastic dystonia is the inability to relax a muscle leading to a spontaneous tonic contraction. Both spasticity and spastic dystonia are present in patients who are at rest; however, only patients with spasticity are actually able to kept their muscles relaxed prior to muscle stretch. The idea that has inspired the present work is that also in patients with spastic dystonia the stretch reflex is likely to be hyper-excitable. Therefore, velocity-dependent hypertonia could be mediated not only by spasticity, but also by spastic dystonia. Methods: Tonic stretch reflexes in the rectus femoris muscle were evoked in 30 patients with multiple sclerosis showing velocity-dependent hypertonia of leg extensors and the habituation of the reflex was studied. Moreover, the capability of relax the muscle prior to muscle stretch (spastic dystonia) was also investigated. Results: A tonic stretch reflex was evoked in all the enrolled patients. 73% of the patients were able to relax their rectus femoris muscle prior to stretch (spasticity). In the overwhelming majority of these patients, the tonic stretch reflex decreased during repeated stretches. In the remaining 27% of the subjects, the muscle was tonically activated prior to muscle stretch (spastic dystonia). In the patients in whom spastic dystonia progressively increased over the subsequent stretches (50% of the subjects with spastic dystonia), the habituation of the reflex was replaced by a progressive reflex facilitation. Discussion: This study shows for the first time that velocity-dependent hypertonia can be caused by two distinct phenomena: spasticity and spastic dystonia. The habituation of the tonic stretch reflex, which is a typical feature of spasticity, is replaced by a reflex facilitation in the half of the subject with spastic dystonia. These preliminary findings suggest that differentiating the two types of velocity-dependent muscle hypertonia (spasticity and spastic dystonia) could be clinically relevant.